Analysis of Disparity in Judges' Decisions in Narcotics Crimes Cases: Case Study of the Decision of the Sungailiat District Court Number 175/PID. SUS/2017/PN SGL JO Supreme Court Decision Number 629 PK/PID. SUS/2024 - Selvy, Selvy; Yandi, Yandi (Journal of Law, Politic and Humanities, 2025)
The disparity in judges' decisions regarding narcotics cases in Indonesia has become a critical issue, affecting legal certainty and public trust in the judicial system. This study examines the decision disparity in the Sungailiat District Court Case No. 175/Pid.Sus/2017/PN Sgl and Supreme Court Case No. 629 PK/Pid.Sus/2024. Using a normative and empirical juridical approach, the study identifies key factors influencing decision differences, including variations in judicial interpretation, application of legal provisions, and consideration of mitigating/aggravating circumstances. By employing Gustav Radbruch's theory of justice and Muladi's integrative criminal theory, the analysis highlights the tension between legal certainty, justice, and societal interests. The findings suggest that disparities arise due to judicial discretion, evidentiary differences, and systemic legal inconsistencies. The research underscores the need for more standardized sentencing guidelines to minimize inconsistencies and enhance fairness in narcotics-related verdicts. The study’s implications contribute to the discourse on judicial transparency, criminal law reform, and the need for a more balanced approach between punishment and rehabilitation in Indonesia’s legal system